Desequilíbrio de ligação e análise de seleção genômica em cana-de-açúcar - Oliveira, Ivone de Bem (2014)
Linkage disequilibrium (LD) is a genetic phenomenon, since it directly interferes in the genetic dynamics of populations. Its effect is observed in the non independent segregation of alleles of different loci, resulting in a correlation between them during the haplotype formation. Any factor that alters allele frequencies can interfere in its dynamics. Both evolutionary factors considered in population genetics and the events used in breeding programs affect the linkage equilibrium/disequilibrium balance. As the microevolutionary factors are specific for each population (natural or from breeding), the LD should be assessed specifically in each population. Specific measures of LD were developed considering the different factors involved in order to mitigate their bias during measurement. Aiming to measure the LD in Ridesa breeding populations a model to predict the LD in polyploids was implemented, using the R platform, based on the Raboin et al. (2008) equations, that considers the sugarcane genome inherent attributes (polysomy and polyploidy). By using this model the LD decay profile was obtained for two breeding populations from Ridesa, the first one composed by 91 individuals from the cross between the RB97327 and RB72454 elite clones and the second from the 81 individuals derived from the selfing of the RB97327 clone. A total of 850 and 470 loci of DArT markers, respectively, were evaluated for each population. The populations showed a high LD, suggesting the existence of linkage disequilibrium even between loci that are 30cM apart. Based on the values found and on other sugarcane LD studies found in literature, the possible effect of the processes of genetic improvement on the dynamics of sugarcane LD were discussed. A second study was carried out associating the mendelian segregation analysis of loci and their effect on the LD pattern, that showed that the LD profiles over increasing distances between loci can be associated to the allelic dosage. Furthermore, aiming to illustrate one of the uses of LD in breeding programs a genomewide selection (GWS) study was developed using RR-BLUP methodology. This study was carried out as a proof of concept, in order to study the feasibility of the method of genome-wide selection in sugarcane. For this, the 132 genotypes were characterized for six different characters, namely: stalk weight (kg), stalk diameter (mm), stalk length (m), soluble solids concentration (Brix), internodes number and stalk number per plot. In addition to demonstrate the great potential of these studies in sugarcane using DArT, the results suggest the existence of a strong effect of intrapopulation structure and of the spurious associations between the loci in the accuracy of the model. These factors, usually ignored in this kind of analysis, should be further investigated in future studies.